FEARCF: Graph-based software library for multidimensional free energy simulations - Bruce-Chwatt, Tomas (Department of Chemistry, 2023)
This thesis presents the efforts to adapt the Free Energy from Adaptive Reaction Coordinate Forces (FEARCF) method into the form of a software library, enabling it to be interfaced with other molecular dynamics (MD) software packages. There exist many methods to calculate the free energy of molecular systems, an important quantity when studying chemical reactions and molecular structures. One of these, FEARCF, was developed at the Scientific Computing Research Unit (SCRU). Previously, this method was restricted to usage within the CHARMM MD software package. Taking inspiration from graph theory and object-orientated design, a successful software library implementation will be demonstrated by presenting results from a range of theories including: classical, ab initio and QM/MM. Simulations are conducted for a range of systems and reaction coordinates including: water, glucose, and the GlcNAc/OGT enzyme-substrate complex.